KEEFEKTIFAN LAYANAN BIMBINGAN KELOMPOK BERMUATAN NILAI SAPRAHAN UNTUK MENINGKATKAN RASA PERSATUAN SISWA DI SMP NEGERI 11 PONTIANAK - Nadia, Lia; Halida; Amallia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low sense of unity among students, characterized by increasing individualism, low social participation, and a lack of tolerance in school interactions. This research is based on the theory of group guidance (Prayitno) and the concept of saprahan values ​​as local wisdom, which emphasizes togetherness, mutual cooperation, religiosity, and strengthening social character. The method used was an experimental design with a pre-experimental design with a one-group pretest and posttest design. The subjects were eight students from SMP Negeri 11 Pontianak, selected purposively. Data collection used a Likert-scale questionnaire to measure the level of unity before and after the treatment. Data analysis was conducted using normality tests, homogeneity tests, and paired sample t-tests. The results showed an increase in the average sense of unity score from 68.63 to 76.88, with an average increase of 40%. The statistical test showed a significance value of p = 0.042 (<0.05), thus accepting the alternative hypothesis. This finding proves that group guidance services containing Saprahan values ​​are effective in increasing students' sense of unity. Therefore, integrating Saprahan values ​​into guidance services can be an innovative strategy for strengthening the sense of togetherness in schools.